2011
DOI: 10.1002/ptr.3589
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antipsoriatic Activity of Aloe Vera Leaf Extract Using a Mouse Tail Model of Psoriasis

Abstract: Aloe vera gel is used traditionally for the treatment of skin diseases, including psoriasis. An ethanolic extract of the gel was assessed for antipsoriatic activity using a mouse tail model of psoriasis. The extract produced a significant differentiation in the epidermis, as seen from its degree of orthokeratosis (85.07 ± 3.36%) when compared with the negative control (17.30 ± 4.09%). This was equivalent to the effect of the standard positive control, tazarotene (0.1%) gel, which showed a 90.03 ± 2.00% degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Aloe showed its ability to reduce the clinical symptoms of psoriasis [41]. Aloe extract showed anti-psoriatic activity of 81.95%, compared with 87.94 for tazarotene in the mouse tail model of psoriasis [42]. Localized side effects including dryness, stinging, soreness, fissures, erythema and contact urticaria may develop after using topical Aloe [25, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Aloe showed its ability to reduce the clinical symptoms of psoriasis [41]. Aloe extract showed anti-psoriatic activity of 81.95%, compared with 87.94 for tazarotene in the mouse tail model of psoriasis [42]. Localized side effects including dryness, stinging, soreness, fissures, erythema and contact urticaria may develop after using topical Aloe [25, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that administration of concentrated isofl avone-rich soy extract for 6 months caused a statistically signifi cant increase in the thickness of gluteal skin epithelium in the postmenopausal women (Accorsi-Neto et al 2009). Also, in the mouse tail model for psoriasis, an ethanolic extract of Aloe vera leaf gel applied topically caused a signifi cant increase in relative epidermal thickness compared to controls (Dhanabal et al 2011). Pain et al (2011 demonstrated a signifi cant increase in epidermal thickness in skin biopsies incubated for 72 h with Achillea millefolium extract compared to controls incubated in culture medium alone.…”
Section: Fig 1 O Hypericifolium Oil In Uvb Non-irradiated (Group 3mentioning
confidence: 97%
“…It is used in constipation, cancer, intestinal worms, cough, and psoriasis. It is cathartic, hypoglycemic, and anti-psoriatic (Dhanabal, Priyanka, Muruganantham, & Vadivelan, 2012). Aloe vera is used in psoriasis topically and to clear psoriatic plaques.…”
Section: Aloe Veramentioning
confidence: 99%